2013
DOI: 10.1371/journal.pone.0069167
|View full text |Cite|
|
Sign up to set email alerts
|

Norepinephrine Inhibits Macrophage Migration by Decreasing CCR2 Expression

Abstract: Increased incidences of infectious and septic complications during post-burn courses represent the main contributor to burn injury mortality. Sustained increases in catecholamine levels, especially norepinephrine (NE), contribute to immune disturbances in severely burned patients. The precise mechanisms underlying NE-mediated immunoregulation are not fully understood. Here we hypothesize that persistently elevated NE levels are associated with immunodysfunctions. We examined the effects of NE on the phenotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…CCR2 is highly expressed on proinflammatory monocyte populations and, although β2AR has been shown to modulate chemotaxis, our findings are novel in that they directly link decreased hematopoietic cell β2AR expression with a corresponding reduction in CCR2 levels and CCL2-dependent migration. Previous studies have shown either no effect of sympathetic nervous system (SNS) stimulation on CCR2 expression in peripheral blood mononuclear cells (28) or decreased CCR2 expression in BM with SNS stimulation (29). These differences may be due to the lack of specificity of norepinephrine and epinephrine treatment and activation of multiple adrenergic receptor subtypes.…”
Section: Discussionmentioning
confidence: 98%
“…CCR2 is highly expressed on proinflammatory monocyte populations and, although β2AR has been shown to modulate chemotaxis, our findings are novel in that they directly link decreased hematopoietic cell β2AR expression with a corresponding reduction in CCR2 levels and CCL2-dependent migration. Previous studies have shown either no effect of sympathetic nervous system (SNS) stimulation on CCR2 expression in peripheral blood mononuclear cells (28) or decreased CCR2 expression in BM with SNS stimulation (29). These differences may be due to the lack of specificity of norepinephrine and epinephrine treatment and activation of multiple adrenergic receptor subtypes.…”
Section: Discussionmentioning
confidence: 98%
“…All animal procedures were Murine bone marrow isolation was conducted as previously described. 17 Briefly, for experiments carried out in differentiating macrophages, total bone marrow cells were treated with various doses of glucose (7Á5, 10 and 12Á5 mM) or various doses of palmitate (0Á1, 0Á2 and 0Á4 mM) or in combination (10 mM glucose plus 0Á2 mM palmitate) during the differentiation period. Macrophages were then harvested on day 7.…”
Section: Animals and Isolation Of Mouse Bone Marrow-derived Macrophagesmentioning
confidence: 99%
“…17 Internalization ability was evaluated at the percentage or mean fluorescence intensity of FITC-positive cells gated on the CD11b + F4/80 + BMM or gated on THP-1 cells.…”
Section: Phagocytosis Assaymentioning
confidence: 99%
“…One possible explanation for this finding includes NOR. Recently, Xiu et al (2013) examined the effects of NOR on the phenotype and functions of bone marrow-derived macrophages. They found that low NOR doses (<10 6 M) inhibited MHCII and CCR2 (chemokine receptor type II) expression and bone marrow-derived macrophage proliferation.…”
Section: Low Percentages Of Cd3mentioning
confidence: 99%